Nanozymes: A New Disease Imaging Strategy - Wang, Peixia; Wang, Tao; Hong, Juanji; Yan, Xiyun; Liang, Minmin (Frontiers in Bioengineering and Biotechnology, 2020)
Nanozymes are nanomaterials with intrinsic enzyme-like properties. They can specifically catalyze substrates of natural enzymes under physiological condition with similar catalytic mechanism and kinetics. Compared to natural enzymes, nanozymes exhibit the unique advantages including high catalytic activity, low cost, high stability, easy mass production, and tunable activity. In addition, as a new type of artificial enzymes, nanozymes not only have the enzyme-like catalytic activity, but also exhibit the unique physicochemical properties of nanomaterials, such as photothermal properties, superparamagnetism, fluorescence, etc. By combining the unique physicochemical properties and enzyme-like catalytic activities, nanozymes have been widely developed for in vitro detection and in vivo disease monitoring and treatment. Here we mainly summarized the applications of nanozymes for disease imaging and detection to explore their potential application in disease diagnosis and precision medicine.